Success in Academic Surgery Part 1 - Chen, Herbert; Kao, Lillian S.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
How does one become a successful academic surgeon?  The Association for Academic Surgery  has been teaching this to medical students, residents, and young faculty for the over 20 years and this is the first time the experience and lessons learned have been summarized in a book format.  Success in Academic Surgery, Part 1, reinforces the curriculum of the Association for Academic Surgery courses and also provides guidance to individual surgeons who have not had the opportunity to attend these courses. Thus, this book is a valuable reference for medical students, surgical residents, and young surgical faculty.
Why Be an Academic Surgeon? Impetus and Options for the Emerging Surgeon-Scientist -- Timeline for Promotion/Overview of an Academic Career -- Reviewing the Literature/Developing a Hypothesis, Study Design -- Ethics in Surgical Research -- Analyzing Your Data -- Animal Models for Surgical Research -- Health Services Research -- Surgical Educational Research: Getting Started -- Translational Research and New Approaches: Genomics, Proteomics, and Metabolomics -- How to Write and Revise a Manuscript for Peer Review Publication -- Choosing, and Being, a Good Mentor -- Writing a Grant/Obtaining Funding -- Setting Up a “Lab” (Clinical or Basic Science Research Program) and Managing a Research Team -- Work-Life Balance and Burnout -- Time Management.
Keywords: Surgery; Surgery; General Surgery